2010
DOI: 10.1177/104063871002200528
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma Bovis Outbreak in a Herd of North American Bison (Bison Bison)

Abstract: Abstract. A disease outbreak of high morbidity and high mortality in bison (Bison bison) was investigated. Clinical signs included lameness, swollen joints, respiratory distress, and lethargy. Fifty-three of 194 animals died. Cows between 5 and 10 years of age were the most affected group, in which 40 of 88 animals died. Necropsies were performed on several animals. There were abscesses in the lung and liver, as well as fibrinosuppurative pleuritis, polyarthritis, and disseminated microabscesses in various org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…Bovine mycoplasmosis, especially associated with M. bovis infection, is spreading globally, including in North America, Europe, and Japan (32)(33)(34)(35)(36). M. bovis is a highly contagious pathogen, and there are no effective vaccines owing to its immunosuppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine mycoplasmosis, especially associated with M. bovis infection, is spreading globally, including in North America, Europe, and Japan (32)(33)(34)(35)(36). M. bovis is a highly contagious pathogen, and there are no effective vaccines owing to its immunosuppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…It has not generally been considered a significant infectious disease threat to bison, with only occasional anecdotal reports of outbreaks of pneumonia. In recent years, however, there have been alarming increases not only in the incidence and severity of M. bovis-associated infections in bison but also in the variety of clinical presentations, which currently include pneumonia, polyarthritis, pharyngitis, placentitis, and abortion (2)(3)(4)(5). Particularly of concern is the observation that M. bovis, which typically is a secondary or tertiary pathogen, appears to be acting as a primary pathogen in bison.…”
mentioning
confidence: 99%
“…Although the usefulness of the Bio-X M. bovis ELISA in bison testing was demonstrated earlier (Register et al 2013a) the possibility of false positive results in this study cannot be excluded. Nevertheless it has been previously demonstrated that M. bovis does infect bison and can cause serious disease problems (Dyer et al 2008, Janardhan et al 2010, Register et al 2013b. Further studies are required to show the true mycoplasma status of bison and to determine the cause of the lesions observed.…”
Section: Resultsmentioning
confidence: 99%
“…In Poland serological evidence in one bison (Krzysiak et al 2014); pneumonia, larynCorrespondence to: K. Dudek, e-mail: katarzyna.dudek@piwet.pulawy.pl, tel. : +48 0-81 889 30 21 gitis, arthritis, synovitis and tenosynovitis in feedlot bison (Dyer et al 2008); arthritis, pleuritis and abscesses in the lung with mortality above 27% (Janardhan et al 2010); fatal reproductive disorders and abortion in American bison in which bronchopneumonia, pleuritis and coagulation necrosis in the lung were also observed (Register et al 2013b . Specific antibodies to these mycoplasmas in bison have not been observed (Krzysiak et al 2014).…”
Section: Introductionmentioning
confidence: 99%